How the Internet is changing the experience of bereavement by suicide: a qualitative study in the UK. - Chapple, A; Ziebland, S (SAGE Publications, 2011)
The aim of this qualitative study was to explore how Internet support may be changing the experiences of people who have been bereaved by suicide. Forty narrative interviews about the (whole) experience of being bereaved by suicide were conducted with a maximum variation sample of people living in the UK. Interviews were transcribed for thematic analysis. The analysis explores several ways in which the Internet has made a difference to the aftermath of the death. These include the use of e-mail and social networking sites to inform others about the death, making sense of the events and gaining support from an Internet community of others who had been similarly bereaved and setting up website memorials. A few people preferred not to use the Internet for this purpose or had no access to a computer. Few adverse consequences of Internet communities were mentioned. In conclusion we found evidence that the Internet is transforming the experience of bereavement by suicide, most dramatically through providing access to other people's experiences.